A Case of Diprosopus: Perinatal Counseling and Management. (31st August 2014) - Thornton, Kimberly M.; Bennett, Timothy; Singh, Vivekanand; Mardis, Neil; Linebarger, Jennifer; Kilbride, Howard; Voos, Kristin
Abstract : Diprosopus is a rare congenital malformation associated with high mortality. Here, we describe a patient with diprosopus, multiple life-threatening anomalies, and genetic mutations. Prenatal diagnosis and counseling made a beneficial impact on the family and medical providers in the care of this case.